Matter and spirit in the universe : scientific and religious preludes to modern cosmology - Kragh, Helge, 1944- (History of modern physical sciences ;, 2004)
Cosmology is an unusual science with an unusual history. This bookexamines the formative years of modern cosmology from the perspectiveof its interaction with religious thought. As the first study of itskind, it reveals how closely associated the development of cosmologyhas been with considerations of a philosophical and religiousnature.